2019
DOI: 10.26508/lsa.201900422
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosalectin LecB impairs keratinocyte fitness by abrogating growth factor signalling

Abstract: This study provides a novel function of the bacterial lectin LecB, which dampens cell proliferation and survival by targeting the insulin-like growth factor-1 for degradation, without receptor activation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 69 publications
(71 reference statements)
0
13
0
Order By: Relevance
“…This makes it on one hand more robust for the bacterium to trigger the desired response, but it also makes it difficult for us to isolate a detailed mechanistic picture of LecB action at the apical cell membrane. We hypothesize that LecB has, due to being a tetramer that offers four binding sites ( 42 ), the capacity to cross-link and cluster different receptors ( 19 , 43 ), which is a general mechanism to activate receptor-mediated signaling cascades at the cell membrane. The data we present here provide two independent lines of evidence for this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…This makes it on one hand more robust for the bacterium to trigger the desired response, but it also makes it difficult for us to isolate a detailed mechanistic picture of LecB action at the apical cell membrane. We hypothesize that LecB has, due to being a tetramer that offers four binding sites ( 42 ), the capacity to cross-link and cluster different receptors ( 19 , 43 ), which is a general mechanism to activate receptor-mediated signaling cascades at the cell membrane. The data we present here provide two independent lines of evidence for this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…1 H NMR (500 MHz, CHCl 3 -d) δ 14.99 (br s, 1H, COOH), 8.77 (s, 1H, ArH-2), 8.02 (d, J = 13.0 Hz, 1H, ArH-5), 7.37 (d, J = 6.7 Hz, 1H, ArH-8), 3.55 (br s, 1H, cPr-H), 3.43 (s, 2H, HCCCH 2 −), 3.41 (br s, 4H, 2x piperazine-CH 2 −), 2.84 (br s, 4H, 2x piperazine-CH 2 ′ −), 2.33 (s, 1H, alkyne-H), 1.39 (d, J = 6.3 Hz, 2H, cPr-CH 2 ), 1.20 (br s, 2H, cPr-CH 2 ′). 13 C NMR (126 MHz, CHCl 3 -d) δ 177.28 (C4O), 167.17 N-Butynyl-ciprofloxacin (21). Ciprofloxacin (500 mg, 1.5 mmol, 1 eq.)…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…( 14 , 15 ) In the case of the d -mannose( d -Man)- and l -fucose( l -Fuc)-binding LecB, da Silva et al recently showed that it organizes the localization of the exopolysaccharide Psl in the biofilm matrix. 19 Further, both lectins also play roles in the direct infection process: LecB conveys virulence through carbohydrate-dependent inhibition of human ciliary beating, 20 interference with repair of wounded tissues, 21 , 22 and activation of B-cells. 23 Next to its biofilm-related roles, it was shown that the d -galactose-binding LecA triggers host cell signaling pathways 24 and mediates membrane invaginations after binding to its cellular receptor, the glycosphingolipid Gb3.…”
Section: Introductionmentioning
confidence: 99%
“…39 On the other hand, LecB facilitates and sustains an infection by adhesion to glycoconjugates on host tissue and inhibition of both airway ciliary beating 40 and wound tissue healing. 41,42 Interestingly, LecB can also activate murine B cells in a carbohydrate-dependent manner in murine infection models. 43 The high genetic diversity and adaptability of P. aeruginosa results in a wide range of clinical isolates with varying characteristics.…”
Section: ■ Introductionmentioning
confidence: 99%